"achJA, dann kenn ich das auch!" Managing Understanding and Knowledge: On Teaching Response Tokens in the German Language Classroom. Issue 2 (September 2016) - Taleghani‐Nikazm, Carmen
Abstract : This paper offers an instructional unit on the response token achja in everyday German conversation. The paper first provides a description of achja and its distinctive prosodic features based on empirical research in conversation analysis. The goal of the paper is to provide instructors of German with information and guidance to integrate authentic and natural conversational data in their teaching and to provide their L2 learners with opportunities to examine, practice, compare, and reflect on some of the ways in which Germans manage and negotiate knowledge and information. In addition, this paper provides hands‐on materials for teaching language and pragmatics suitable for novice to intermediate students.